The Effect Of Combination Of Super Red Dragon Fruit Extract (Hylocereus Costaricensis) + Fe Tablets On Increasing Hemoglobin Levels In Pregnant Women In Trimester Iii With Anemia - Sherllia Sofyana (Institute of Computer Science (IOCS), 2022)
Anemia in pregnancy, namely hemoglobin <11gram/dl for the first and third trimesters, and <10.5 grams/dl for the second trimester. Super red dragon fruit (Hylocereus costaricensis) is one of the many alternatives used to help prevent anemia in pregnancy. Objective: To determine the effect of the combination of super red dragon fruit extract + Fe tablets on the average increase in hemoglobin in third trimester pregnant women with anemia. Objective To determine the effect of the combination of super red dragon fruit extract + Fe tablets on the average increase in hemoglobin of pregnant women in the third trimester with anemia. The results of the intervention group were the pretest hemoglobin level of 9.352 grams/dL and the post-test hemoglobin level of 10.845 grams/dL with p value <0.05, while the pretest control group had a hemoglobin level of 9.202 grams/dL and a posttest hemoglobin level of 10,635 grams/dL with a p value <0.05. There is an effect of the combination of super red dragon fruit extract + Fe tablets on the increase in hemoglobin levels